Solid state composite electrolyte comprising aramid polymer fibrils

By using aramid polymer fibrils to reinforce inorganic solid electrolytes, the problem of insufficient mechanical strength in thin solid composite electrolytes is solved, resulting in a high-strength, flexible, and thermally stable solid electrolyte suitable for solid-state batteries.

CN115398734BActive Publication Date: 2026-11-06DUPONT SAFETY & CONSTRUCTION INC
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202180022175.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-17
Filing Date
2021-03-15
Publication Date
2026-11-06
Estimated Expiration
2041-03-15

AI Technical Summary

Technical Problem

Existing technologies make it difficult to manufacture very thin solid composite electrolytes with high mechanical strength and flexibility, especially due to the insufficient mechanical strength of inorganic solid electrolytes and the unsuitability of large-size pulp fiber reinforcements for very thin electrolytes.

Method used

Using aramid polymer fibrils as reinforcing materials, an inorganic solid electrolyte is mixed with 1 to 30 weight percent of aramid polymer fibrils and then solidified by applying pressure and heating to form a solid composite electrolyte with a thickness of 5 to 1000 micrometers. The aramid polymer fibrils have a diameter of 10 to 2000 nanometers, a length of 0.2 to 3 millimeters, a specific surface area of ​​3 to 40 square meters per gram, and a Canadian standard freeness of 0 to 100 milliliters.

Benefits of technology

It achieves enhanced mechanical properties, improved flexibility, avoids cracking, and provides solid-state composite electrolytes with thicknesses from 5 to 1000 micrometers, suitable for solid-state batteries, with high strength, high modulus, toughness and thermal stability, and does not require additional polymer binders.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115398734B_ABST
    Figure CN115398734B_ABST
Patent Text Reader

Abstract

A solid-state composite electrolyte suitable for use in a solid-state battery, and a battery comprising the same, the solid-state composite electrolyte comprising 70 to 99 weight percent of an inorganic solid electrolyte and 1 to 30 weight percent of aromatic polyamide polymer fibrils, based on the total weight of the inorganic solid electrolyte and the aromatic polyamide fibrils in the solid-state composite electrolyte, wherein the aromatic polyamide polymer fibrils have: i) a diameter of 10 to 2000 nanometers, ii) a length of 0.2 to 3 millimeters, iii) a specific surface area of 3 to 40 square meters per gram, and iv) a Canadian Standard Freeness of 0 to 100 milliliters; the solid-state composite electrolyte having a thickness of 5 to 1000 micrometers.
Need to check novelty before this filing date? Find Prior Art

Description

Background Technology

[0001] This invention relates to fiber-reinforced solid composite electrolytes suitable for use in solid-state batteries.

[0002] Yersak et al.'s publication "Hot Pressed, Fiber-Reinforced (Li2S)" 70 (P2S5) 30 Solid-State Electrolyte Separators for Li Metal Batteries (Hot-pressed, fiber-reinforced (Li2S) for Li metal batteries) 70 (P2S5) 30 The paper "[Solid Electrolyte Membrane]" (ACS Appl. Energy Mater., 2019, 2, pp. 3523-3531) discloses a (Li2S) membrane reinforced with aramid fibers by hot pressing at 240 °C and 200 MPa. 70 (P2S5) 30 Densification of solid-state electrolyte composite electrolyte membranes. This publication further discloses data on composite electrolyte thicknesses ranging from 540 to 920 micrometers and provides photographs of a single thin composite electrolyte sample with a thickness of 100 micrometers. As confirmed by the SEM images in this publication, the aramid fiber pulp itself occupies a large area in the cross-section of the composite electrolyte.

[0003] With the development of more efficient, lightweight, and versatile batteries, there has been a growing desire for the ability to manufacture solid-state electrolytes of a wide range of thicknesses, including the flexibility to manufacture very thin solid-state composite electrolytes. In some cases, solid-state composite electrolytes with thicknesses less than 100 micrometers are desired, and in others, thicknesses significantly less than 100 micrometers are desirable. However, the development of such thinner solid-state electrolytes has been hampered by the lower mechanical strength of inorganic solid-state electrolytes, requiring reinforcement. Furthermore, as illustrated in the publications of Yersak et al., large-sized pulp fibers are impractical as reinforcements for very thin solid-state composite electrolytes. Therefore, what is needed is a suitable fiber reinforcement for solid-state composite electrolytes suitable for use in solid-state batteries, allowing for manufacturing flexibility, including the ability to manufacture very thin solid-state composite electrolytes. Summary of the Invention

[0004] This invention relates to a solid composite electrolyte suitable for use in solid-state batteries, comprising 70 to 99 weight percent of an inorganic solid electrolyte and 1 to 30 weight percent of aromatic polyamide polymer fibrils, based on the total weight of the inorganic solid electrolyte and the aromatic polyamide fibrils in the solid composite electrolyte, wherein the aromatic polyamide polymer fibrils have:

[0005] i) Diameters ranging from 10 to 2000 nanometers,

[0006] ii) Length of 0.2 to 3 mm,

[0007] iii) Specific surface area of ​​3 to 40 square meters per gram, and

[0008] iv) 0 to 100 ml of Canadian standard free concentration;

[0009] The solid composite electrolyte has a thickness of 5 to 1000 micrometers.

[0010] The present invention also relates to a method for manufacturing a solid composite electrolyte suitable for use in solid-state batteries, comprising the following steps:

[0011] a) Combining 70 to 99 parts by weight of inorganic solid electrolyte and 1 to 30 parts by weight of aromatic polyamide polymer fibrils based on 100 total parts of inorganic solid electrolyte and aromatic polyamide fibrils to form a mixture;

[0012] b) The mixture is solidified by applying pressure and heating for a time sufficient to form a solid composite electrolyte with a thickness of 5 to 1000 micrometers;

[0013] The aromatic polyamide polymer fibrils described herein have:

[0014] i) Diameters ranging from 10 to 2000 nanometers,

[0015] ii) Length of 0.2 to 3 mm,

[0016] iii) Specific surface area of ​​3 to 40 square meters per gram, and

[0017] iv) 0 to 100 ml of Canadian standard free concentration. Attached Figure Description

[0018] Figure 1 This is a digital photograph of aramid polymer fibers taken at 1000x magnification.

[0019] Figure 2 This is a digital photograph of commercially available aramid pulp taken at 500x magnification.

[0020] Figure 3This is a diagram comparing the pore distribution in PPD-T / PVP filaments with that in PPD-T filaments.

[0021] Figure 4 This is a highly idealized representation of a very thin solid composite electrolyte reinforced with aramid pulp.

[0022] Figure 5 This is a highly idealized representation of a very thin solid composite electrolyte reinforced with aramid polymer fibrils. Detailed Implementation

[0023] This invention relates to a solid composite electrolyte suitable for use in solid-state batteries and a solid-state battery comprising the solid composite electrolyte. The solid composite electrolyte comprises 70 to 99 weight percent of an inorganic solid electrolyte and 1 to 30 weight percent of aromatic polyamide polymer fibrils, based on the total weight of the inorganic solid electrolyte and aromatic polyamide fibrils in the composite electrolyte. In some preferred embodiments, the aromatic polyamide polymer fibrils are the only fibrous component in the composite electrolyte. The aromatic polyamide polymer fibrils have a diameter of 10 to 2000 nanometers, a length of 0.2 to 3 millimeters, a specific surface area of ​​3 to 40 square meters per gram, and a Canadian standard freeness of 0 to 100 milliliters.

[0024] Solid-state batteries (SSBs) are battery technologies that use solid electrodes and solid electrolytes instead of the liquid or polymer gel electrolytes present in lithium-ion or lithium-polymer batteries. The term "solid-state composite electrolyte" refers to a solid electrolyte made from inorganic materials that are further reinforced with fibers to enhance the mechanical properties of the solid electrolyte. Preferably, the fiber material is uniformly distributed throughout the solid-state composite electrolyte.

[0025] As used herein, the term "battery" is intended to include not only batteries, but also things such as capacitors and other devices having: (1) a cathode, (2) an anode, (3) a physical separation device between the cathode and anode to help prevent short circuits, and (4) some type of electrolyte. Specifically, in solid-state batteries, the solid electrolyte also serves as a battery separator located between the positive plate (cathode) and the negative plate (anode), and provides a structural separation between these oppositely charged electrodes while allowing the electrolyte to help current flow through the separator.

[0026] It is believed that using very small-diameter aromatic polyamide polymer fibrils as fiber reinforcements in solid composite electrolytes enhances their mechanical properties; and is particularly useful in very thin solid composite electrolytes, as the smaller fibers are better and more uniformly distributed throughout the solid composite electrolyte. The addition of aromatic polyamide polymer fibrils is also thought to improve the flexibility of solid composite electrolytes, allowing them to withstand a certain degree of flexural deformation without the formation of undesirable cracks.

[0027] As used herein, the term "aromatic polyamide" refers to an aromatic polyamide in which at least 85% of the amide (-CONH-) bonds are directly attached to two aromatic rings. Optionally, additives may be used with the aromatic polyamide and may be dispersed throughout the polymer structure. It has been found that up to about 10% by weight of other supporting materials can be blended with the aromatic polyamide. It has also been found that copolymers in which up to about 10% of other diamines replace the diamines of the aromatic polyamide or up to about 10% of other diacyl chlorides replace the diacyl chlorides of the aromatic polyamide can be used.

[0028] As used herein, the term "aromatic polyamide polymer fibrils" refers to hair-like fibrous materials having a diameter of 10 to 2000 nanometers, preferably 10 to 1200 nanometers, made of aromatic polyamide polymers or polymer blends containing at least two polymers (in which a majority amount (greater than 50% by weight) of the aromatic polyamide polymer is present). Figure 1 These are representative digital photographs of aramid polymer fibers. The aramid polymer fibers further have a preferred length of 0.2 to 3 mm. The term "length" as used herein for fibrous materials (such as aramid polymer fibers and pulp) refers to a measured "length-weighted average" length. In some preferred embodiments, the aramid polymer fibers are refined aramid polymer fibers made from flocs by exposing the flocs to a refining step that shears the flocs into smaller aramid polymer fibers. In some preferred embodiments, the aramid polymer fibers have a length of 0.4 to 3 mm, preferably 0.8 to 3 mm.

[0029] It is believed that the diameter of aromatic polyamide polymer fibrils affects the pore size of solid composite electrolytes, and that aromatic polyamide polymer fibrils with diameters greater than 2000 nm produce solid composite electrolytes with undesirable high pore sizes, which may ultimately lead to microcracks and short circuits in the electrolyte. Furthermore, it is believed that aromatic polyamide polymer fibrils with diameters less than 10 nm or lengths less than approximately 0.2 mm do not contribute to the mechanical strength of solid composite electrolytes; therefore, it is desirable for most aromatic polyamide polymer fibrils to have a length of 0.2 mm or greater. In addition, the small diameter of aromatic polyamide polymer fibrils is advantageous for the use of fibrous materials in very thin solid composite electrolytes.

[0030] The aromatic polyamide polymer fibrils further have an aspect ratio that can range from about 150 to 300,000. Aspect ratio is also known as length divided by diameter, and the phrases “aspect ratio,” “ratio of average length to diameter,” and “length to diameter” are used interchangeably herein. In some embodiments, the ratio of the average length to diameter of the aromatic polyamide polymer fibrils is about 1000 or greater. In some embodiments, the aromatic polyamide polymer fibrils have an average length to diameter ratio of about 3000 or less. In some preferred embodiments, the ratio of the average length to diameter ranges from about 1000 to 3000. A higher average length to diameter ratio of the aromatic polyamide polymer fibrils is considered to contribute to better mechanical reinforcement of the composite electrolyte and thus to its better mechanical properties.

[0031] Since qualitative measurements of certain fibrous materials, such as aramid polymer fibrils, can be difficult, comparisons can be made by measuring the "freeness" of these materials. The most popular techniques for measuring freeness are the Canadian Standard Freeness (CSF) or the Schopper-Riegler Freeness (SRF).

[0032] The inventors consider the Canadian Standard Freeness (CSF) to be a preferred technique for characterizing the aramid polymer fibrils used herein. Aromatic polyamide polymer fibrils are preferably manufactured by refining aramid polymer fibers or flocs to produce fibrils; such fibrils preferably have a CSF of 0 to 50 ml, and in some embodiments, a CSF of 0 to 20 ml. CSF is an indicator of the fineness of the aramid polymer fibrils or the degree to which they are fibrillated during refining, wherein very fine aramid polymer fibrils have very low CSF. A low CSF value also indicates fibrils of uniform size, as materials with a wide size distribution typically have high CSF values.

[0033] The aramid polymer fibrils defined herein are fibrous materials and differ from existing aramid polymer pulps. Such aramid polymer pulps are preferably manufactured by refining flocs, or can be manufactured directly from the components taught in U.S. Patent Nos. 5,202,184; 5,523,034; and 5,532,034. However, such methods not only provide fibrous materials with a wider range of fiber sizes and lengths, but also, due to the difficulty in controlling such methods, can produce both “stalks” and fibrils extending from the stalks, where the stalks are typically columnar residues of the original aramid polymer flocs and have a diameter of about 10 to 50 micrometers. Furthermore, in the case of aramid polymer pulp, the length measurement is understood to be the length of the pulp’s stalk characteristics, which is also referred to as “pulp stalks.”

[0034] Furthermore, the average length-to-diameter ratio of aramid polymer fibrils is much greater than that of conventional aramid polymer pulp, such as that produced by the methods described in U.S. Patent Nos. 5,084,136; 5,171,402; and 8,211,272, which is considered to have an average length-to-diameter ratio typically less than 150; or much greater than that of highly refined pulp, such as that disclosed in U.S. Patent Publications 2016 / 0362525 and 2017 / 0204258, which is considered to have an average length-to-diameter ratio less than that of conventional pulp (e.g., typically less than 100).

[0035] Furthermore, aramid polymer fibrils used in composite electrolytes are essentially stalkless or stalkless aramid polymer fibrils. As used herein, the term "stalkless aramid polymer fibrils" means that, by optically measuring the fibril sample at 500x or 1000x magnification, at least 95% by weight of the fiber material is an aramid polymer fibril with a desired diameter of 10 to 2000 nanometers. In some embodiments, by optically measuring the fibril sample at 500x or 1000x magnification, at least 98% by weight of the fiber material is an aramid polymer fibril with a desired diameter of 10 to 2000 nanometers. In some embodiments, by optically measuring the fibril sample at 500x or 1000x magnification, 100% by weight of the fiber material is an aramid polymer fibril with a desired diameter of 10 to 2000 nanometers.

[0036] A preferred method for producing stalk-free aromatic polyamide polymer fibrils is to refine fibers or flocs made from polymer blends containing at least two polymers, wherein the majority (greater than 50% by weight) of the aromatic polyamide polymer is present. A preferred polymer blend is a polymer blend of 80 to 96% by weight of poly(p-phenylene terephthalamide) (PPD-T) and 4 to 20% by weight of polyvinylpyrrolidone (PVP). When refining aromatic polyamide fibers or aromatic polyamide flocs made from this PPD-T / PVP polymer blend, the resulting fibrous material is substantially entirely fibrils, and there are essentially no larger stalks in the material, such as... Figure 1 As shown in the digital photograph, it is believed that at least 4% by weight of PVP must be present in the virgin fibers or flocs in order to refine the fibers or flocs into virgin fibers with virtually no stalk remaining. This is consistent with... Figure 2 This is shown in comparison to conventional refined aromatic polyamide pulp with visible stems, made from poly(p-phenylene terephthalamide) homopolymer (PPD-T).

[0037] It has been found that filaments made from blends of 80 to 96 wt% PPD-T and 4 to 20 wt% PVP exhibit significantly different porosity and crystal properties compared to filaments composed solely of PPD-T. In this document, the terms "fiber" and "filament" are used interchangeably. Fibers spun directly from a polymer solution onto bobbins without cutting are generally referred to as continuous fibers or continuous filaments, and multifilament yarns comprise multiple continuous filaments.

[0038] Figure 3 This illustrates the difference in X-ray scattering between the two types of filaments. Curve 20 represents a PPD-T / PVP blend filament, while curve 30 represents a filament made solely of PPD-T. Curve 30 shows that the PPD-T filament has a significant peak concentrated at approximately 2 Å (and a much smaller peak concentrated at approximately 4 Å), indicating very small pores in the fiber. Curve 20 shows that the PPD-T / PVP blend has a much wider pore size distribution, with one peak concentrated at approximately 3 Å and a very broad sloping peak concentrated at approximately 250 Å, but extending through a region of approximately 70 to 600 Å. This is thought to indicate that the filament made from the PPD-T / PVP blend has a very large number of pores that are much larger than those in the PPD-T filament.

[0039] Furthermore, it is believed that due to this difference in fiber crystallinity and pore structure, when the filaments are mechanically refined, the result is much finer and more uniformly distributed fibrils, such as... Figure 1 As shown in the diagram. In other words, the very high crystallinity and low porosity of PPD-T fibers are considered to mean that when mechanically refined, the refining shearing action primarily abrades the surface of the filaments, resulting in a typical stalk structure with fibrils (as shown in the diagram). Figure 2 (As shown); while the lower crystallinity and high porosity of PPD-T / PVP blend filaments make them more readily separated into single refined fibrils under the same shear force; they have a greater quantity of smaller and relatively more uniform diameter fibrils, and more importantly, are essentially stalk-free (i.e., stalk-free). Aromatic polyamide polymer fibrils are considered to have a relatively uniform diameter, with a total diameter size range of approximately 300 nanometers, as visually measured by SEM micrographs.

[0040] Aromatic polyamide polymer fibrils are preferably made from aromatic polyamide flocs having PPD-T as the majority of the polymeric material component by weight and at least one other polymeric material component; these components are preferably immiscible with each other, such that the at least two polymeric materials exist in the flocs as closely mixed but separate solid phases. When such aromatic polyamide flocs are refined, they produce aromatic polyamide polymer fibrils having domains of two different polymeric materials; one phase is a continuous or primary polymeric phase or a PPD-T polymer, and the other phase is a discontinuous or secondary polymeric phase (preferably a PVP polymer).

[0041] The discontinuous or subpolymer phase is considered to exist as small nanoscale domains in the material, which permeate the flocculent and act as interruptions in the flocculent structure during refining to facilitate rapid and more complete refining of the flocculent into fibrils. After refining, a portion of the discontinuous or subpolymer from each interruption point remains on or at the surface of each fibril produced by the refining process.

[0042] Aromatic polyamide polymer fibrils also possess high surface areas. The terms "surface area," "specific surface area," and "BET surface area" are used interchangeably in this text. Aromatic polyamide polymer fibrils have a surface area of ​​approximately 3 to 40 μm. 2 Specific surface area per g. In some embodiments, the specific surface area is 6 m². 2 / g or greater; in some embodiments, the specific surface area is 8m². 2 / g or greater. A particularly preferred range for specific surface area is 6 to 20 m². 2 / g.

[0043] In contrast, conventional pulp refined from flocculents made from miscible blends of polymeric materials or polymeric materials that do not have discontinuous subpolymer domains will not have this high surface area. Furthermore, if the flocculent is refined sufficiently to have this measured high surface area, the resulting pulp particles will have this low aspect ratio (caused by a very low average length), and they will not provide adequate reinforcement for the composite material.

[0044] Preferred aromatic polyamide fibrils contain 80 to 96 weight percent of poly(p-phenylene terephthalamide) (also known as poly(p-phenylene terephthalamide) or PPD-T and used herein). PPD-T means a homopolymer produced by molar-to-molar polymerization of p-phenylenediamine and terephthaloyl dichloride, and a copolymer produced by the combination of small amounts of other diamines with p-phenylenediamine and small amounts of other diacyl chlorides with terephthaloyl dichloride. Generally, other diamines and other diacyl chlorides may be used in amounts up to about 10 mol% of p-phenylenediamine or terephthaloyl dichloride, or possibly slightly higher, provided that the other diamines and diacyl chlorides do not have reactive groups that interfere with the polymerization reaction. PPD-T also refers to copolymers obtained by combining other aromatic diamines with other aromatic diacyl chlorides, such as 2,6-naphthaloyl chloride, chloroterephthaloyl chloride, or dichloroterephthaloyl chloride; provided that the other aromatic diamine and aromatic diacyl chloride are present in an amount that allows for the preparation of anisotropic spinning solutions. The preparation of PPD-T is described in U.S. Patent Nos. 3,869,429; 4,308,374; and 4,698,414.

[0045] Preferred aromatic polyamide fibrils also contain 4 to 20 weight percent of poly(vinylpyrrolidone) (also known as polyvinylpyrrolidone or PVP and used herein). PVP refers to a polymer produced by the linear polymerization of monomer units of N-vinyl-2-pyrrolidone and containing small amounts of comonomers that may be present at concentrations below those that do not interfere with the interaction between PVP and PPD-T. PVP with molecular weights from as low as about 5,000 to as high as about 1,000,000 can be used. Very high molecular weight PVP produces high-viscosity spinning solutions. PVP with a molecular weight of about 10,000 to about 360,000 is preferred.

[0046] The solid-state composite electrolyte comprises an inorganic solid electrolyte and aromatic polyamide polymer fibrils. In some embodiments, the inorganic solid electrolyte comprises lithium sulfide, lithium oxide, a mixture of lithium sulfide and lithium oxide, phosphorus sulfide, or any mixture of these sulfides / oxides. In some embodiments, the inorganic solid electrolyte comprises lithium sulfide or a blend of lithium oxide and phosphorus sulfide. In some preferred embodiments, the inorganic solid electrolyte comprises a) a blend of 60 to 80 weight percent lithium sulfide or lithium oxide or a mixture thereof, and b) a blend of 20 to 40 weight percent phosphorus sulfide, based on the total weight of a) and b) in the inorganic solid electrolyte. In some most preferred embodiments, the inorganic solid electrolyte comprises a) a blend of 70 to 80 weight percent lithium sulfide or lithium oxide or a mixture thereof, and b) a blend of 20 to 30 weight percent phosphorus sulfide, based on the total weight of a) and b) in the inorganic solid electrolyte.

[0047] Inorganic solid electrolytes may also be selected from zirconium oxide, germanium compounds, silicon compounds, or mixtures thereof. In addition to the previously mentioned sulfides and / or oxides, these may be used in amounts of 20% by weight or more based on the total weight of the inorganic solid electrolyte; or alone in solid composite electrolytes.

[0048] The solid composite electrolyte comprises 70 to 99 weight percent of an inorganic solid electrolyte and 1 to 30 weight percent of aromatic polyamide polymer fibrils, based on the total weight of the inorganic solid electrolyte and aromatic polyamide fibrils in the composite electrolyte. It is believed that the solid composite electrolyte will have improved properties when the total weight of the inorganic solid electrolyte and aromatic polyamide fibrils in the composite electrolyte has at least one weight percent of aromatic polyamide polymer fibrils; furthermore, the improvement in properties decreases when the composite electrolyte has more than 30 weight percent of aromatic polyamide polymer fibrils. In some embodiments, the solid composite electrolyte has at least 3 weight percent of fibrils, based on the total weight of the inorganic solid electrolyte and aromatic polyamide fibrils in the composite electrolyte. In some other embodiments, the solid composite electrolyte has at least 5 weight percent of fibrils, based on the total weight of the inorganic solid electrolyte and aromatic polyamide fibrils in the composite electrolyte. In some embodiments, the solid composite electrolyte has 20 weight percent or less of fibrils, while in some other embodiments, the solid composite electrolyte has 15 weight percent or less of fibrils, both embodiments based on the total weight of the inorganic solid electrolyte and aromatic polyamide fibrils in the composite electrolyte. In some embodiments, the solid composite electrolyte has 5 to 15 weight percent of fibrils, based on the total weight of the inorganic solid electrolyte and the aromatic polyamide fibrils in the composite electrolyte.

[0049] Solid-state composite electrolytes possess a number of preferred properties. These preferred properties include desired thickness, desired fracture toughness, and desired ionic conductivity. Flame-retardant fiber reinforcement is also desirable. Preferred solid-state composite electrolytes are non-flammable because they can be manufactured solely from inorganic electrolytes and aromatic polyamide polymer fibrils, without the need for additional polymer binders. Aromatic polyamide polymer fibrils, as defined herein, are inherently fire-resistant when used as reinforcing materials. Aromatic polyamide polymer fibrils also possess a unique combination of high strength, high modulus, toughness, and thermal stability (stable up to 350°C), as well as electrochemical compatibility with a wide range of electrode materials.

[0050] Solid-state composite electrolytes have a thickness of 5 to 1000 micrometers. This thickness range is compatible with the typical space available for solid-state composite electrolytes as separators in SSBs. Solid-state composite electrolyte thicknesses less than 5 micrometers are not considered sufficiently robust to withstand battery manufacturing steps, and thicknesses greater than 1000 micrometers have limited applicability due to the confined space in typical batteries; additionally, such thicker solid-state composite electrolytes increase costs, which is undesirable. In some embodiments, the thickness of the solid-state composite electrolyte is 10 micrometers or greater; in some embodiments, the thickness is 800 micrometers or less. In some embodiments, the thickness of the solid-state composite electrolyte is 700 micrometers or less, and in some specific applications, the thickness is 400 micrometers or less. A preferred solid-state composite electrolyte thickness range is 10 to 700 micrometers. Another preferred solid-state composite electrolyte thickness range is 15 to 450 micrometers. Extremely thin solid-state composite electrolytes are also desirable in some cases, those with a thickness of 100 micrometers or less; thin electrolytes with a thickness range such as 10 to 95 micrometers are particularly desirable.

[0051] Figure 4 and 5 The value of aromatic polyamide polymer fibrils relative to pulp in a very thin solid composite electrolyte is illustrated in an idealized way. Figure 4 This is an idealized representation of a very thin solid composite electrolyte 45 reinforced with a large amount of aramid pulp 40; and Figure 5 This is an idealized representation of a very thin solid composite electrolyte 55 reinforced with aramid polymer fibrils 50. Although the composite electrolytes or fiber materials in these figures are not drawn strictly to scale, they are... Figure 4 It is understandable that as the thickness of composite materials decreases, the large size of aramid pulp may become a problem due to the excessive volume or cross-sectional area occupied by the pulp within the composite. However, as... Figure 5 As shown, aromatic polyamide polymer fibrils, which have much smaller nanoscale dimensions, occupy a much smaller relative volume or cross-sectional area in composite materials, providing the advantages already stated herein.

[0052] Solid-state composite electrolytes preferably have a strength of 0.5 to 10 MPa·m². 1 / 2 The fracture toughness of the electrolyte is important because solid electrolytes such as sulfide glasses are inherently brittle due to their glass-ceramic state. This is one of the significant challenges in manufacturing methods that produce inorganic electrolytes without generating macroscopic or microscopic cracks. (Less than 0.5 MPa) 1 / 2 The fracture toughness is undesirable because such brittle structures are difficult to handle without damage. (Values ​​greater than 10 MPa / m)1 / 2 The fracture toughness is considered to be the upper limit of the reinforcement provided by the addition of aramid polymer fibrils. In some embodiments, the solid composite electrolyte preferably has a fracture toughness of at least 0.5 MPa. 1 / 2 The fracture toughness. In some embodiments, the solid composite electrolyte preferably has a fracture toughness of 5 MPa m. 1 / 2 Or even lower fracture toughness. A preferred solid-state composite electrolyte has a fracture toughness range of 1 to 5 MPa / m. 1 / 2 .

[0053] Solid-state composite electrolytes preferably have an ionic conductivity of 0.1 to 100 millisiemens per centimeter (mS / cm). This range is important because ionic conductivity affects the performance of solid-state electrolyte batteries. Ionic conductivity less than 0.1 mS / cm is undesirable because it is practically too low for use in batteries; that is, such ionic conductivity results in a very low coulombic efficiency (CE) at room temperature, also known as Faraday efficiency or current efficiency, which describes the charging efficiency of electron migration within the battery. In some embodiments, the solid-state composite electrolyte preferably has an ionic conductivity of at least 0.1 mS / cm. In some embodiments, the solid-state composite electrolyte preferably has an ionic conductivity of 50 mS / cm or less. A preferred range of ionic conductivity for a solid-state composite electrolyte is 1 to 50 mS / cm. Another preferred range is 1 to 25 mS / cm.

[0054] Aromatic polyamide polymer fibrils are preferably manufactured by spinning a continuous filament from a dope solution containing an aromatic polyamide polymer, cutting the continuous filament yarn into flocs, and then mechanically refining the flocs into fibrils using one or more refining machines. In a preferred method, the dope is a solution containing a combination of PPD-T polymers and PVP polymers in sulfuric acid. Exemplary representative methods for manufacturing continuous filament yarns are found in U.S. Patent Nos. 5,073,440 and 5,094,913 and U.S. Patent Publication US2006 / 0113700. The aromatic polyamide flocs are then cut from the continuous filament yarn. Prior to refining, the aromatic polyamide flocs typically have a length of about 2 mm to about 25.4 mm, in some cases 2 to 10 mm, or even 3 to 10 mm.

[0055] Aromatic polyamide polymer fibrils are preferably produced from flocs by refining or fibrillating PPD-T / PVP flocs using techniques familiar to paper, such as cutting, pulverizing, or abrading the PPD-T / PVP flocs using dry and wet disc or cone refining, hydrauling, and beating. Preferably, refining is carried out on a dispersion of the flocs in water, and preferably the dispersion is refined multiple times by passing it through a refining machine. That is, the refined dispersion leaving the refining machine is recycled through the same refining machine or a second refining machine for a second pass, and so on. The starting dispersion typically has a solids content of about 1 to 4% by weight of the flocs in water.

[0056] If the flocculent is a PPD-T / PVP flocculent, it can be fully fibrillated into stalk-free aramid polymer fibrils after only three passes through a refining machine, and then suitable for manufacturing solid composite electrolytes. Stalk-free aramid polymer fibrils have a very low Canadian Standard Freeness (CSF) compared to pulp made from fibers that tend to fibrillate into a mixture containing a large amount of stalks combined with the fibrils. While suitable fibrils are produced by three passes through a refining machine, additional passes through the refining machine, up to 20 or more, can be used for further distribution and homogenization of the fibrils, provided the final strength of the solid composite electrolyte is not negatively affected. Preferably, the fibrils are produced by cycling the dispersion through the refining machine 3 to 20 times; in some embodiments, 3 to 10 passes through the refining machine are used.

[0057] It is believed that if subsequent processes after the refining step are used to separate or recover fibrils from the stalk, stalk-free aromatic polyamide polymer fibrils can be obtained with sufficient care from more conventional PPD-T, acrylic, or cellulose pulps. It is envisioned that if such fibrils meet the definition of "stalk-free" as described herein, they would be suitable fibrils for use in composite electrolytes.

[0058] Solid-state composite electrolytes suitable for use in solid-state batteries can be manufactured via a method comprising the following steps: combining 70 to 99 parts by weight of an inorganic solid electrolyte and 1 to 30 parts by weight of an aromatic polyamide polymer fibrils based on 100 total parts to form a mixture; and consolidating the mixture by applying pressure and temperature for a time sufficient to form a solid-state composite electrolyte having a thickness of 5 to 1000 micrometers; wherein the aromatic polyamide polymer fibrils have a diameter of 10 to 2000 nanometers, a length of 0.2 to 3 millimeters, a specific surface area of ​​3 to 40 square meters per gram, and a Canadian standard freeness of 0 to 100 milliliters. The method for producing the solid-state composite electrolyte utilizes one or more inorganic solid electrolytes and the same aromatic polyamide polymer fibrils as previously contemplated and described herein, including all the various features and embodiments already provided herein.

[0059] Once refined, it is considered that the fibril-water mixture can be directly mixed with the inorganic electrolyte, followed by water removal; or the fibrils can first be separated from the water and optionally dried, and then mixed with the inorganic electrolyte. The mixture of inorganic electrolyte and aromatic polyamide polymer fibrils can then be densified, for example, by pressing in a mold under high pressure, such as 150 MPa to 300 MPa or slightly higher. If desired, the mixture can be preheated before applying pressure, preferably to 240°C or higher, for 10 minutes or longer, followed by applying pressure while maintaining the temperature for one hour or longer. If desired, the solid electrolyte can be further annealed by removing the pressure but maintaining the temperature on the sample for 30 minutes or longer.

[0060] Solid-state composite electrolytes can be used to fabricate solid-state batteries, including the anode, cathode, and solid-state composite electrolyte. For example, solid-state batteries (SSBs) with non-flammable solid electrolytes (SEs) can achieve significant energy density leaps by using lithium (Li) metal anodes. A major obstacle to the development of all-solid-state Li batteries is the low ionic conductivity of SEs at room temperature. Inorganic ceramic-based solid electrolytes have been developed to increase ionic conductivity. One promising inorganic ceramic electrolyte with high ionic conductivity for SSBs is the LPS (binary Li₂S-P₂S₅) sulfide glass electrolyte, which exhibits an ionic conductivity greater than 10⁻³ S / cm at room temperature.

[0061] Test methods

[0062] Use the following test method in the examples provided below.

[0063] thickness Measured according to ASTM D374-99 and reported in mils and converted to micrometers.

[0064] fracture toughness Measured according to ASTM C1421-10 "Standard Test Methods for Determination of Fracture Toughness of Advanced Ceramics at Ambient Temperature".

[0065] Ion impedance Measured according to ASTM D7148-13 and in milliohm-cm 2 Report to the unit.

[0066] Freeness. The Canadian Standard Freeness (CSF) of fibrils or pulp was measured using a Canadian Standard Freeness Tester Model 33-23, supplied by Testing Machines Inc., Newcastle, DE, according to standard test method TAPPI T 227. CSF measures the ease with which water drains from the aqueous pulp or dispersion of fibrils / pulp and is inversely correlated with the degree of fibrillation of the pulp, as a larger number of fibrils will reduce the rate at which water drains through the pad formed during the test. Data obtained from the test under standard conditions are expressed in milliliters of water drained from 3 grams of pulp in 1 liter of water. Lower values ​​indicate that more fibrillated pulp will retain more water and drain more slowly.

[0067] Freeness. The Schopper-Riegler Freeness Ratio (SRF) is determined according to BS EN ISO 5267-1 2001. The Schopper-Riegler test is designed to provide a measure of the rate at which a diluted suspension of pulp can be dewatered. SR Freeness (filtration performance) can be expressed as the Schopper-Riegler degree. The fiber material to be tested is prepared according to the test conditions defined in the ISO standard described above. 1000 ml of the prepared pulp is poured into the drain chamber. The discharge from the bottom and side holes is collected. The filtrate from the side holes is measured in a special cylinder marked with an SR degree scale. 1000 ml of discharge corresponds to 0 Schopper-Riegler degree, while 0 ml of discharge corresponds to 100 Schopper-Riegler degree.

[0068] Fiber length. The length of the fiber material (“length-weighted average” length) is measured according to the TAPPI test method T 271.

[0069] The ratio of average length to diameterThis is calculated by dividing the "length-weighted average" length of the virgin fiber or pulp by its corresponding average visually measured diameter. The "length-weighted average" length refers to the length calculated according to the following formula.

[0070]

[0071] Where n is the number of fibrils or pulp stalks, and l is the length of a single fibril or pulp stalk (pulp stalk).

[0072] The width of a single fibril or pulp stalk is obtained by visually measuring the width of the fibril or pulp stalk at several points (at least three) along the length of the fibril or pulp from photomicrographs taken at 500x or 1000x magnification. Average "visual measurement diameter" This is performed on at least a dozen fibrils or pulp stalks drawn in a photomicrograph, and the average visual measurement of the fiber diameter is calculated.

[0073] The fiber and / or pulp were measured using a Fiber Expert benchtop analyzer supplied by Metso Automation Inc., Kajaani, Finland. "Length-weighted average" length Spend As the pulp flows through the analyzer, the analyzer uses a digital CCD camera to capture photographic images of the fibrous material dispersed in water to form the pulp, and an integrated computer analyzes the fibers in these images to calculate their length as a weighted average, expressed in millimeters. The “length-weighted average” length of the pulp is measured using an LS200 laser diffraction analyzer supplied by Beckman Coulter Inc., Miami, FL, and expressed in micrometers.

[0074] Specific surface area The specific surface area of ​​dried fibrous materials (including fibrils) was measured by nitrogen adsorption / desorption at liquid nitrogen temperature (77.3 K) using a Micromeritics ASAP 2405 porosimeter, and expressed as square meters per gram (m²). 2 Units are expressed as per g. Unless otherwise indicated, samples were degassed overnight at 150°C prior to measurement, and weight loss was determined by adsorbed moisture. Five-point nitrogen adsorption isotherms were acquired in the relative pressure range of P / P0 from 0.05 to 0.20 and analyzed according to the BET method (S. Brunauer, PHEmmett, and E. Teller, J. Am. Chem. Soc. [Journal of the American Chemical Society] 1938, 60, 309); P is the equilibrium pressure above the sample, and P0 is the saturation pressure of the sample, typically greater than 760 Torr.

[0075] use Wide-angle and small-angle X-rays Scattering test method is used to measure crystallinity and porosity.

[0076] Instruments: Rigaku Micromax 007 custom pinhole SAXS system or advanced photon source DND-CAT (segment 5), ID-D line.

[0077] X-ray source: For Rigaku instruments: rotating anode copper kα1 source. APS radiation energy is variable, but typically around 9 keV is used.

[0078] Detector: Bruker Vantec 2000 2048x2048 pixel 2D detector, for Rigaku; simultaneous data acquisition was performed using a group of three MAR detectors in the APS, positioned at wide, medium, and small angles. An unwarping routine was used in the Vantec 2000 data acquisition software to correct for inherent spatial and intensity fluctuations in the detector.

[0079] Sample mounting: WAXS: Straighten the yarn length using collodion solution; cut into small pieces and fix the single layer to the sample plate. SAXS: Wrap the fiber around the grooved sample plate ten times and secure with tape. The plate has a hole in the middle of the fiber bundle for X-ray transmission.

[0080] Data Acquisition: Rigaku: Data is acquired for 1 / 2 hour per sample under vacuum; APS data acquisition is typically 5 frames per second, run in air. This is performed twice, once with an attenuator (for high intensity at low q) and once without an attenuator. The data are stitched together at different distances / attenuation points.

[0081] Example

[0082] Reference Example A

[0083] The following samples are prepared to be suitable for manufacturing solid composite electrolytes in the following examples using aramid polymer fibrils. The polyvinylpyrrolidone (PVP) polymer sold under the name K30-P is available from BASF. The poly(p-phenylene terephthalamide) (PPD-T) polymer is manufactured using a generic polymerization process as generally disclosed in the following U.S. Patent Nos. 3,869,429; 4,308,374; and 4,698,414.

[0084] PPD-T polymer / PVP polymer blend fibers are manufactured by forming separate polymer solutions and spinning fibers according to a general procedure shown in U.S. Publication US2006 / 0113700 by Hartzler et al. The first solution is 19.5 wt% PVP in sulfuric acid and is prepared by mixing PVP in sulfuric acid at room temperature. The second solution is also 19.5 wt% PPD-T in sulfuric acid. The PVP polymer solution and the PPD-T solution are then combined and mixed to form a spinning solution having a polymer blend. This is accomplished by injecting the PVP polymer solution centerline into a line carrying the PPD-T polymer solution via a gear pump, followed by a static mixer. This forms dispersed PVP polymer solution particles in a continuous PPD-T polymer solution phase.

[0085] Fiber yarns are manufactured by extruding a spinning solution containing a polymer blend through a spinneret with multiple spinneret orifices to form solution filaments. Specifically, a spinning solution containing the previously described polymer blend is air-gap spun into multifilament yarn by extruding the solution through a 0.8 cm air gap through a 667-orifice spinneret with an orifice diameter of 0.063 mm into a water coagulation bath containing approximately 5% sulfuric acid at a temperature of 5 degrees Celsius. The multifilament yarn is then washed and neutralized to remove the sulfuric acid solvent and dried and wound onto bobbins.

[0086] Cut the yarn into 0.25-inch (0.20 cm) long pieces.

[0087] The flocculents were then refined using an aqueous pulp containing 2% flocculent material through a single-disc 12-inch Andritz laboratory refiner. PPD-T / PVP fibrils were fully formed in the refiner after only 3 passes. Samples were taken for testing, and the material was refined again after 3 passes. Additional samples were taken for testing, and the material was refined again after 3 passes. Table 1 provides data on the resulting fibrils (indicating very fine fibrils obtainable with only 3 passes), including data on Canadian Standard Freeness (CSF) and Schopper-Riegler Freeness (SRF). After only 3 passes in the refiner, the PPD-T / PVP blend flocculents were fully fibrillated into fibrils with zero CSF. Increasing the refinement time, i.e., increasing the number of passes through the refiner, shortened the length of the nanofibrils. For comparison with the data in Table 1, the PPD-T pulp produced via a 3-pass refiner has approximately 300 ml of CSF.

[0088] Table 1

[0089]

[0090] Various compositions of PPD-T / PVP blended fibrils were then compared with commercially available 100% PPD-T pulp from DuPont, Wilmington, DE. Table 2 provides characterization information on fibrils manufactured from flocs with different PPD-T / PVP blends and those manufactured via a three-pass refining machine. Characterization of 100% PPD-T pulp manufactured via a three-pass refining machine is also shown.

[0091] Figure 3 Curve 20 is for the 87 / 13 PPD-T / PVP blend, and Table 2 shows that the apparent crystal size (ACS 110) of the PPD-T / PVP blend filaments is reduced relative to 100% PPD-T filaments when PVP is included, and the PPD-T / PVP filaments have much larger pore sizes and pore size distributions that are completely different from those of curve 30 (which represents PPD-T filaments used to manufacture conventional PPD-T pulp).

[0092] Table 2

[0093]

[0094] Reference Example B

[0095] The following preparation is used to prepare a sample of an inorganic electrolyte containing 75 mol% lithium sulfide (Li₂S) and 25 mol% phosphorus sulfide (P₂S₅) suitable for use in the manufacture of the following examples of solid composite electrolytes. The inorganic electrolyte mixtures of Li₂S (Sigma Aldrich, 99.98%) and P₂S₅ (Sigma Aldrich, 99%) were combined and mechanically ground at 500 rpm in a planetary ball mill apparatus using a ZrO₂ grinding bowl and 110 g of ZrO₂ balls with a diameter of 3 mm in an argon atmosphere in a glove box at room temperature for at least 20 hours.

[0096] Individual composite granule samples were formed by pressing 200 mg of the mixture into a circular mold at 300 MPa. The composite granule samples were then first heated to 240°C for 10 minutes, and then maintained at this temperature while applying a pressure of 150–200 MPa for 1 hour. The pressure was then released, and the composite granule samples were further annealed at the same temperature for 30 minutes to remove any remaining mechanical stress from the densification process. The composite granule samples were then allowed to cool for several hours before further testing.

[0097] Examples 1 to 4

[0098] Four separate samples of the aromatic polyamide polymer fibrils from Reference Example A were each combined with four separate samples of the inorganic electrolyte mixture from Reference Example B to produce four separate samples of inorganic electrolyte having 1, 3, 5, and 10 weight percent of aromatic polyamide polymer fibrils, respectively. The four separate samples were then mixed in an ultrasonic mixer at 2,000 rpm for 10 min.

[0099] Composite granules containing inorganic electrolytes and aromatic polyamide polymer fibrils are formed by pressing four separate samples as in Reference Example B.

[0100] Compare examples A to D

[0101] Examples 1 through 4 were repeated; however, the aramid polymer fibrils of Reference Example A were replaced with 100% commercially available PPD-T pulp (Style 1F361, available from DuPont, Wilmington, Delaware). The pulp was not stalk-free as defined herein and had a Canadian standard freeness of 260 ml and a 9m³ after drying. 2 / g specific surface area. The composite granules containing both inorganic electrolyte and PPD-T pulp were formed by pressing four separate samples as in Reference Example B.

[0102] discuss

[0103] Visual inspection of the cross-sections of the composite granules in Examples A through D reveals large visible areas of aramid pulp. These large areas will obviously pose a problem for very thin composites. Visual inspection of the cross-sections of the composite granules in Examples 1-4 reveals finely distributed aramid polymer fibrils, resulting in a structure more suitable for very thin composites.

Claims

1. A solid composite electrolyte suitable for use in solid-state batteries, comprising: The solid composite electrolyte comprises 70 to 99% by weight of an inorganic solid electrolyte and 1 to 30% by weight of an aromatic polyamide polymer fibrils, based on the total weight of the inorganic solid electrolyte and the aromatic polyamide fibrils in the solid composite electrolyte. The aromatic polyamide polymer fibrils are stalkless refined fibrils, and the aromatic polyamide polymer comprises a blend of polymers containing 80 to 96 weight percent poly(p-phenylene terephthalamide) and 4 to 20 weight percent poly(vinylpyrrolidone); and The aromatic polyamide polymer fibrils described herein have: i) A diameter of 10 to 2000 nanometers, wherein the aromatic polyamide polymer fibrils have a total diameter range of 300 nanometers. ii) Length of 0.2 to 3 mm, iii) Specific surface area of ​​3 to 40 square meters per gram, and iv) 0 to 100 ml of Canadian standard free concentration; The solid composite electrolyte has a thickness of 5 to 95 micrometers and a strength of 0.5 to 10 MPa. ½ Fracture toughness.

2. The solid composite electrolyte as described in claim 1, wherein, The inorganic solid electrolyte comprises lithium sulfide, lithium oxide, or a mixture thereof.

3. The solid composite electrolyte as described in claim 2, wherein, The inorganic solid electrolyte comprises a blend of the following: a) 60 to 80% by weight lithium sulfide or lithium oxide or mixtures thereof, and b) 20 to 40 percent by weight of phosphorus sulfide, Based on the total weight of a) and b) in the inorganic solid electrolyte.

4. The solid composite electrolyte as described in claim 1, wherein, The inorganic solid electrolyte contains 20% by weight or more of zirconium oxide, germanium compound, silicon compound, or mixtures thereof, based on the total weight of the inorganic solid electrolyte.

5. The solid composite electrolyte as claimed in claim 1, having an ionic conductivity of 0.1 to 100 millisiemens per centimeter (mS / cm).

6. A solid-state battery comprising an anode, a cathode, and a solid-state composite electrolyte as described in claim 1.

7. A method for manufacturing a solid composite electrolyte suitable for use in solid-state batteries, comprising the following steps: a) Combining 70 to 99 parts by weight of inorganic solid electrolyte and 1 to 30 parts by weight of aromatic polyamide polymer fibrils based on 100 total parts to form a mixture; b) The mixture is solidified by applying pressure and heating, sustained to a thickness of 5 to 95 micrometers and a strength of 0.5 to 10 MPa m. ½ The fracture toughness of solid composite electrolytes over time; The aromatic polyamide polymer fibrils are stalkless refined fibrils, and the aromatic polyamide polymer comprises a blend of polymers containing 80 to 96 weight percent poly(p-phenylene terephthalamide) and 4 to 20 weight percent poly(vinylpyrrolidone); and The aromatic polyamide polymer fibrils described herein have i) A diameter of 10 to 2000 nanometers, wherein the aromatic polyamide polymer fibrils have a total diameter range of 300 nanometers. ii) Length of 0.2 to 3 mm, iii) Specific surface area of ​​3 to 40 square meters per gram, and iv) 0 to 100 ml of Canadian standard free concentration.

8. The method of claim 7, wherein, The inorganic solid electrolyte comprises lithium sulfide, lithium oxide, or a mixture thereof.

9. The method of claim 8, wherein, The inorganic solid electrolyte comprises a blend of the following: a) 60 to 80% by weight lithium sulfide or lithium oxide or mixtures thereof, and b) 20 to 40 percent by weight of phosphorus sulfide, Based on the total weight of a) and b) in the inorganic solid electrolyte.

10. The method of claim 7, wherein, The inorganic solid electrolyte contains 20% by weight or more of zirconium oxide, germanium compound, silicon compound, or mixtures thereof, based on the total weight of the inorganic solid electrolyte.

11. The method of claim 7, wherein, The solid composite electrolyte has an ionic conductivity of 0.1 to 100 millisiemens per centimeter (mS / cm).

Citation Information

Patent Citations

  • Continuous processes for making composite fibers

    US20060113700A1

  • Micropulp-elastomer masterbatches and compounds

    US20160362525A1

  • Micropulp-elastomer masterbatches and compounds

    US20170204258A1

  • High strength polyamide fibers and films

    US3869429A

  • Process for the preparation of poly-p-phenyleneterephthalamide

    US4308374A